Intrauterine left gastric artery infarct as the primary etiology for congenital nonsyndromic microgastria - Sandra Rivera-Beltrán; Adel Gonzalez-Montalvo; Jorge J. Zequeira; Victor N. Ortíz (Elsevier, 2019)
Congenital Microgastria is a rare condition associated with multiple associated anomalies. We present the first case of a newborn female patient diagnosed with isolated microgastria caused by a vascular accident in utero with absence of the left gastric artery. The patient had a 2 month history of gastroesophageal reflux, postprandial emesis, diarrhea, and failure to thrive. It was sequentially treated with nutritional optimization via a Bishop-Koop type proximal jejunal feeding stoma, and subsequent Hunt-Lawrence gastric augmentation. The patient has recovered from surgery and caught up in terms of weight expectancy for age. Keywords: Congenital microgastria, Left gastric artery, Artery infarct, Vascular accident, In utero, Bishop-koop